Alvocidib inhibits IRF4 expression via super‐enhancer suppression and adult T‐cell leukemia/lymphoma cell growth. Issue 12 (3rd October 2022) - Sakamoto, Hikaru; Ando, Koji; Imaizumi, Yoshitaka; Mishima, Hiroyuki; Kinoshita, Akira; Kobayashi, Yuji; Kitanosono, Hideaki; Kato, Takeharu; Sawayama, Yasushi; Sato, Shinya; Hata, Tomoko; Nakashima, Masahiro; et al.
Abstract: Adult T‐cell leukemia/lymphoma (ATL) is an intractable hematological malignancy with extremely poor prognosis. Recent studies have revealed that super‐enhancers (SE) play important roles in controlling tumor‐specific gene expression and are potential therapeutic targets for neoplastic diseases including ATL. Cyclin‐dependent protein kinase (CDK) 9 is a component of a complex comprising transcription factors (TFs) that bind the SE region. Alvocidib is a CDK9 inhibitor that exerts antitumor activity by inhibiting RNA polymerase (Pol) II phosphorylation and suppressing SE‐mediated, tumor‐specific gene expression. The present study demonstrated that alvocidib inhibited the proliferation of ATL cell lines and tumor cells from patients with ATL. RNA sequencing (RNA‐Seq) and chromatin immunoprecipitation sequencing (ChIP‐Seq) disclosed that SE regulated IRF4 in the ATL cell lines. Previous studies showed that IRF4 suppression inhibited ATL cell proliferation. Hence, IRF4 is a putative alvocidib target in ATL therapy. The present study revealed that SE‐mediated IRF4 downregulation is a possible mechanism by which alvocidib inhibits ATL proliferation. Alvocidib also suppressed ATL in a mouse xenograft model. Hence, the present work demonstrated that alvocidib has therapeutic efficacy against ATL and partially elucidated its mode of action. It also showed that alvocidib is promising for the clinical treatment of ATL and perhaps other malignancies and neoplasms as well. Abstract : These results offer novel evidence that SAR1A can function in an oncogenic manner to promote metastasis and to regulate autophagic activity. Knocking down SAR1A can prevent metastasis by modulating the RhoA/YAP, ER stress, and autophagic activities, offering new insight into the mechanisms whereby intratumoral autophagy is regulated and highlighting these pathways as promising targets for therapeutic intervention in osteosarcoma.